Systematic Mapping Studies in Modularity in IT Courses - de L. Lima, Pablo Anderson; da C. C. Franco Fraga, Gustavo; dos Anjos, Eudisley G.; da Silva, Danielle Rousy D. (Computational Science and Its Applications -- ICCSA 2015, 2015)
Modularity is one of the most important quality attributes during system development. Its concepts are commonly used in disciplines of information technology courses, mainly in subjects as software project, software architecture, and others. However, it is notable among certain groups of students that this issue is not fully absorbed in a practical way. Although some researchers and practitioners have approach themes like this, there is still a lack of research about how modularity can be approached in IT courses. This paper presents a systematic mapping study about how the modularity is addressed in education. The main objective is to understand what are the main areas in this field and find more interesting points of research to improve the practice of modularity during IT disciplines.